Differential market entry determinants for for-profit and non-profit long-term care providers - Katsuyoshi Nakazawa (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
This study considers market entry determinants for both for-profit and non-profit at-home long-term care providers in Japan. It examines market structure incentives and barriers to entry using a panel dataset of 48 Japanese municipalities for the 2003-2011 period. Estimation results show that for-profits and non-profits face different determinants of entry. Potential for-profit entrants are sensitive to profit considerations and therefore adapt to the market structure and clear barriers to entry. However, potential non-profits with preferential tax treatment and the constraint of non-distribution of profits enter disadvantaged municipalities. Both profits and non-profits have become integrated in Japanese at-home care markets.
Keywords: C33; I13; L22; L33; R19; 330; Entry; For-profit; Non-profit; Long-term at-home care; SUR